1999
DOI: 10.1103/physrevlett.82.5393
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity Elongation in Polymeric Emulsions

Abstract: Video microscopy is used to measure the shear-induced deformation of dilute emulsions composed of viscoelastic polymer melts. In the limit of strong shear, a transition in which the droplets elongate perpendicular to the flow field is observed. A force-balance argument relates this behavior to the change in first normal stress difference across the droplet interface. [S0031-9007(99)09504-6] PACS numbers: 83.50. Ax, 47.55.Dz, 61.25.Hq, 83.70.Hq When a fluid dispersed in a second fluid is subjected to shear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…The increase in R 3 /R 0 at high capillary number is very dramatic that it can be as high as 3. The drop elongation in vorticity direction was also observed by other researchers [14,17,43,51], however, they did not perform quantitative study of the deformation with accuracy in three dimensions. Mode II resembles the rod-climbing phenomenon and is attributed to the viscoelastic nature of the fluid [14,52].…”
Section: Observations Of Drop Deformationsupporting
confidence: 56%
See 3 more Smart Citations
“…The increase in R 3 /R 0 at high capillary number is very dramatic that it can be as high as 3. The drop elongation in vorticity direction was also observed by other researchers [14,17,43,51], however, they did not perform quantitative study of the deformation with accuracy in three dimensions. Mode II resembles the rod-climbing phenomenon and is attributed to the viscoelastic nature of the fluid [14,52].…”
Section: Observations Of Drop Deformationsupporting
confidence: 56%
“…At such high capillary numbers, the drop deformation and breakup can be very different since elasticity is expected to dominate the deformation process at high shear rate. Hobbie and Migler [14], Migler [43] and Mighri and Huneault [17] found that at high capillary numbers with strong elastic effect, viscoelastic drops under shear elongated and broke up in the vorticity direction, which is the direction perpendicular to the flow direction and the velocity gradient direction. However, there is a lack of quantitative studies on drop deformation in viscoelastic systems sheared at high capillary numbers.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is however, not a general break-up mechanism and can mostly be attributed to the presence of impurities or a nonuniform surfactant distribution along the drop surface (14,15). Other break-up mechanisms have been described in literature, for instance when dealing with viscoelastic components (16,17) or when using microfluidic devices in which confinement effects become important (18,19). Here, however, we focus on bulk behavior of systems with Newtonian components.…”
Section: Ispersing One Fluid In a Second Immiscible Liquid Ismentioning
confidence: 99%